Optimization of aggregate mixture to paver production using linear programming (2017)
This paper presents the optimization of aggregate mixture in the production of paver blocks through the formulation of a linear programming model. The proposed model aims at reducing manufacturing costs, respecting the compliance with the minimum quality requirements and mechanical/physical characteristics required by the technical standards. The results obtained with the model were used to produce a batch of products, which underwent a process of visual inspection of the quality and laboratory tests. The results showed the viability of using a linear programming to define the required quantities of raw materials to the manufacturing process of Concrete Paver Blocks, which generates economic benefits for the industry and allows the product quality control as well.